The Impact of the Government Role in the Development of Small and Medium Enterprises in the Arab Republic of Egypt (Applying to Damietta Governorate) - Afifi, Ehab Mohamed; Abdel Fattah, Mohamed Najib; Muslim, Iman Mustafa (Journal of Economic, Administrative and Legal Sciences, 2023)
Small and medium enterprises are one of the most important pillars of economic development in Egypt and a strategic goal adopted by the Egyptian state because of its vital role in economic development and addressing the problems of poverty and unemployment, so the orientation of small, medium and micro enterprises has become the largest engine of economics to achieve sustainable development, and state institutions are working to adopt an integrated strategy to achieve a real renaissance through these projects and push young people to the direction of establishing small and medium enterprises. Through this research, we addressed the impact of the government role in the development of small and medium enterprises in Egypt by applying to Damietta governorate because of its large number of small and medium enterprises in several areas, the problem of the research is that the more or less the government role supporting these small and medium enterprises is absent, the more negatively this affects the development of these projects. The research was based on several hypotheses, namely the role of the government in finance, legislation, technical support and marketing in the development of small and medium enterprises. The research also showed the most important recommendations recommended by the researcher in this letter represented in recommendations implemented by the various authorities in the country, including recommendations in the short term and others in the long term specified by the entity implementing each entity for the recommendation, whether financing, legislative, marketing or technical support.